The Quarrel over a Carpet, or the Question of Maintaining Order in the Republic. Valencia, Venezuela at the end of the 18th century - Leal Curiel, Carole (Universidad Pedagógica y Tecnológica de Colombia, 2014)
At the end of the 18th century, the city of Valencia, in the province of Venezuela, was the center of a dramatic dispute over the use of carpets in churches, which at irst glance may seem banal. As is demonstrated in this article, the carpet embodies central ideas about order, such as inequality and equality, both legal and natural, which express a conception of society sustained by this inequality, as a fundamental principle for maintaining order. The Valencian people not only accepted and assumedthat life was naturally unequal, but also understood inequality as an expression of their social position, of a hierarchical nature and afirmed by material objects.